POLITICAL SUPPORT IN CENTRAL AND EASTERN EUROPE: THE EFFECT OF PARTY SYSTEM AND COALITION SIZE - Bartasevičius, Vainius (Politologija, 2013)
High figures of political support are a necessary ingredient of consolidated democracy. Although the low standards of both satisfaction with democracy and trust in parliament in CEE countries are well known, one cannot say much about the factors underlying the fluctuation of these two indicators. The paper examines the effect of parliamentary fragmentation, polarization and ruling coalition size on satisfaction with democracy and trust in parliament. Statistical analysis, encompassing 10 CEE countries from 1991 to 2011, is used to measure the impact of political factors, while the effect of economic growth and unemployment rate is also evaluated. The most important statistical techniques used in the research are correlation analysis, linear regression, and a single-factor analysis of variance. Atwo-case comparative analysis is also carried out, with the aim of elaborating one of the findings of statistical analysis. The strongest finding suggests that there is a negative relation between unemployment rate and satisfaction with democracy. Furthermore, satisfaction with a political regime is undermined by a small number of parliamentary parties and large ruling coalitions. Trust in parliament tends to be lower when ideological differences among parliamentary parties are sizable, as well as at the times of economic recession or marginal growth. The fact that satisfaction with democracy and trust in parliament depend on different factors indicates the ability of CEE citizens to distinguish between different political phenomena. This conclusion contradicts the prevalent belief that the political sophistication in CEE countries is low. Generally, there are more winners of democratic competition when a large ruling coalition is formed. However, statistical analysis has shown that large ruling coalitions are usually followed by low satisfaction with democracy. This should be taken as a sign that, in the case of CEE countries, distinction between losers and winners of democratic competition is irrelevant, because citizens tend to turn away from their chosen parties very quickly. Instead, when asked to evaluate the functioning of democracy, they concentrate on the negative consequences of large ruling coalitions. Acomparative analysis of political realities in the Czech Republic and Bulgaria has shown that a large ruling coalition diminishes the political role of parliament, provides a strong ground for the implementation of a strict and unpopular economic policy and leads to the lack of viable political alternatives in the ranks of parliamentary opposition. The complex of these political phenomena contributes to the low satisfaction with democracy.